2019
DOI: 10.4103/apjon.apjon_62_18
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives about Spirituality and Spiritual Care

Abstract: Objective: This study was undertaken to explore the perspectives regarding spirituality and spiritual care held by individuals with advanced disease. The aim was to gain a deeper understanding about their viewpoints surrounding spiritual care and the role of health-care professionals in providing such care. Methods: Sixteen individuals with advanced disease and a prognosis of <12 months underwent an in-depth interview. Transcripts were subjected to a qualitative descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 65 publications
(67 reference statements)
1
45
0
6
Order By: Relevance
“…Individuality as a dimension of spirituality emphasizes the importance of looking at each person and their subjective experience, pointing to the person-centered care whose goal is a meaningful life, which is an important interception between health care and spirituality ( Puchalski, 2013 ; Håkansson Eklund et al, 2019 ). The healthcare professionals should be capacitated in recognizing spiritual issues in their patients and facilitate connections with the appropriate support ( Fitch and Bartlett, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuality as a dimension of spirituality emphasizes the importance of looking at each person and their subjective experience, pointing to the person-centered care whose goal is a meaningful life, which is an important interception between health care and spirituality ( Puchalski, 2013 ; Håkansson Eklund et al, 2019 ). The healthcare professionals should be capacitated in recognizing spiritual issues in their patients and facilitate connections with the appropriate support ( Fitch and Bartlett, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Alswat et al (2017) also suggested that one of the dimensions that obtained the highest positive score in safety culture was related to organizational learning, continuous learning and organizational improvement (16). The study by Fitch and Bartlett (2019), which was conducted to identify systemic factors in nurses' perception of the patient's organizational safety culture, con rms this as well (17). The results of the study carried out by Top and Tekingündüz (2015) on nurses' perception in relation to safety culture showed six important predictors of overall safety perception, one of which was continuous training and upgrading organizational learning (18).…”
Section: Discussionmentioning
confidence: 85%
“…In other words, if a patient achieves a meaningful life it shows that his/her spirituality has been valued, and paying attention to the spirituality of patients while also inducing a sense of worthiness to patients, makes them more receptive to accepting palliative care. This issue has been emphasized from various perspectives in other studies [27][28][29][30][31] such as: paying attention to patient's spirituality as a factor that could help improve patient's quality of life, adapting to the evolving concerns, providing hope for the patient, and finding ways to help patients escape their spiritual crisis and improve their lives.…”
Section: Discussionmentioning
confidence: 99%